GAMBARAN ANTARA KOPING STRESS DENGAN TINGKAT STRESS PADA MAHASISWA TINGKAT AKHIR - Widyastuti, Linda; Amiroh, Siti Nurul; Dea Sukmana, Priscalina (Yayasan Indonesia Bermutu, 2024)
The aim of this study is to comprehend the connection between coping strategies and stress levels among final-year students during thesis writing process. Stress is frequently brought on by challenges with academic writing, data analysis, lecturer guidance, and coping with non-academic matters. Individuals employ coping methods as a means of overcoming and resolving issues. This study uses a qualitative descriptive methodology while doing a literature review. Content analysis was used to examine data from various articles. According to the results, the majority of final-year students report feeling moderately stressed. Emotional and problem-focused coping are the two main types of coping. Students employ a variety of coping strategies, such as asking for social support, participating in uplifting activities, and talking about their concerns with others. Despite their stress, students remain highly motivated to complete their theses. Students' stress levels are also influenced by their age and gender. This study examines coping techniques and stress levels among final-year students. The findings imply that educational institutions should pay more attention to students during the thesis writing process and establish appropriate stress management measures.